Reengineering of business processes of a construction enterprise in conditions of digitalization - Derkach, A. (Ways to Improve Construction Efficiency, 2023)
The etymology of the term "reengineering" was studied, which means a set of methods that the company uses to design and redesign the business in accordance with strategic requirements, where the key aspect is the improvement of the financial condition. Under the influence of digitalization, companies must constantly change in order to meet the needs of consumers and be competitive. At the same time, it is important to model, analyze and redesign complex and outdated business processes that do not meet modern requirements in the conditions of fierce competition on the world market of products and services. The article considers the issue of formalization of reengineering stages, at which business processes are selected and evaluated, taking into account the impact of digitalization on them. A methodology for choosing business processes based on the examination of the most important success factors is proposed. The choice is made on the basis of the analysis of the integral assessment of business processes, taking into account the variability of many experts. A formalized methodology for the first stage of business process reengineering is presented, which pays attention to organized interaction between company specialists and consultants. This approach is designed to reduce the subjectivity of business process assessments, compensating for individual eliminations and increasing the objectivity of the assessment. The formalized nature of the methodology, as well as versatile analysis, including the reasoned reasoning of specialists and managers, contribute to increasing the validity of the decisions made regarding the reengineering of business processes. This is important in order for the changes developed in the processes to be the most effective and meet the strategic goals of the enterprise. Adherence to these principles can help create a more reliable methodology for business process reengineering, providing more accurate and informed assessments, and therefore more effective process improvements